UPAYA MENINGKATKAN KOMPETENSI GURU MELALUI KEGIATAN MUSYAWARAH GURU MATA PELAJARAN (MGMP) DI SMK NEGERI PANGKALAN LESUNG - LASMONO LASMONO (JURNAL ILMIAH KOHESI, 2022)
The problem in this study is that the achievement of targets in MGMP at this vocational high school has not shown adequate results where some teachers have not been able to manage learning properly. the purpose of this study was to describe Efforts to Improve Teacher Competence Through Subject Teacher Consultation (MGMP) Activities at SMK Negeri Pangkalan Lesung. The type of research used in this study is the school action research method (PTS). The research location was carried out at SMK Negeri Pangkalan Lesung. The research was conducted in the January-June semester of 2022. The research subjects were teachers representing SMK Negeri Pangkalan Lesung totaling 20 people. The data collection technique of this school action research is through quantitative data obtained from observation. The data analysis technique used in this research is quantitative data analysis sourced from the acquisition of observation data. The results showed that 1) to improve competence in the learning process was carried out through subject teacher deliberation activities (MGMP) for 2 cycles, each cycle 2 meetings, each meeting conducted 4 stages of activities starting from planning, action implementation, observation and reflection. 2) Observation is carried out by the supervisor as a collaborator of the principal ending with a reflection to see the positive and negative aspects as a basis for planning the next action in cycle 2. With MGMP activities there was an increase in teacher competence at the beginning of the activity 40% cycle I to 62% increased by 22%. In cycle II there was a further increase of 93%, an increase from cycle I to cycle II of 31%.